Efficacy, safety, bone and metabolic effects of HIV nucleoside reverse transcriptase inhibitor BMS-986001 (AI467003): a phase 2b randomised, controlled, partly blinded trial. Issue 1 (January 2016) - Gupta, Samir K; McComsey, Grace A; Lombaard, John; Echevarría, Juan; Orrell, Catherine; Avihingsanon, Anchalee; Osiyemi, Olayemi; Santoscoy, Mario; Ray, Neelanjana; Stock, David A; Joshi, Samit R; Hanna, George J; et al.
Summary: Background: BMS-986001 is a thymidine analogue nucleoside reverse transcriptase inhibitor (NRTI) designed to maintain in-vitro antiviral activity while minimising off-target effects. We assessed the efficacy and safety of BMS-986001 versus tenofovir disoproxil fumarate in treatment-naive patients with HIV-1. Methods: In this phase 2b, randomised, active-controlled trial (AI467003), we recruited treatment-naive (no current or previous exposure to an antiretroviral drug for >1 week) adults (aged at least 18 years) with HIV-1 from 47 sites across Asia, Australia, Europe, North America, South Africa, and South America. Patients with plasma HIV-1 RNA greater than 5000 copies per mL and CD4 counts greater than 200 cells per μL were randomly assigned (2:2:2:3) to receive BMS-986001 100 mg, 200 mg, or 400 mg once a day or to receive tenofovir disoproxil fumarate 300 mg once a day; each allocation was given with efavirenz 600 mg once a day and lamivudine 300 mg once a day. Both patients and investigators were masked to BMS-986001 dose (achieved with similar looking placebo tablets), but not allocation up to and including week 48. The primary endpoints were the proportion of patients with plasma HIV-1 RNA less than 50 copies per mL and safety events (serious adverse events and adverse events leading to discontinuation) through week 24; the main analysis was with a modified intention-to-treat population. Resistance analysis was a secondary endpoint, and additional safety parameters were exploratory endpoints. This trial is registered withClinicalTrials.gov, numberNCT01489046, and the European Clinical Trials Database, number EudraCT 2011-003329-89. Findings: Patients were recruited between Jan 25, 2012, and Oct 3, 2012; 757 patients were assessed for eligibility and 301 were randomly assigned to receive either BMS-986001 once a day (67 patients to 100 mg, 67 to 200 mg, and 66 to 400 mg) or tenofovir disoproxil fumarate (n=101). 297 patients received at least one dose of study drug. At week 24, 57 (88%) of 65 patients for whom there were data in the 100 mg group, 54 (81%) of 67 in the 200 mg group, 62 (94%) of 66 in the 400 mg group achieved HIV-1 RNA less than 50 copies per mL, compared with 88 (89%) of 99 in the tenofovir disoproxil fumarate group (modified intention-to-treat population). BMS-986001 was generally well tolerated through week 48. Two patients had BMS-986001-related serious adverse events (atypical drug eruption and thrombocytopenia) and two in the tenofovir disoproxil fumarate group had study drug-related serious adverse events (potential drug-induced liver injury and depression or lipodystrophy) that led to discontinuation. NRTI resistance-associated mutations were reported in four (2%) of 198 patients, and non-NRTI mutations in 17 (9%) of 198 patients receiving BMS-986001 versus none of 99 and one (1%) of 99 patients receiving tenofovir disoproxil fumarate, respectively. Compared with tenofovir disoproxil fumarate, individuals in the BMS-986001 groups showed a smaller decrease in lumbar spine and hip bone mineral density but greater accumulation of limb and trunk fat, subcutaneous and visceral adipose tissue, and increased total cholesterol. Interpretation: BMS-986001 had similar efficacy to that of tenofovir disoproxil fumarate and was associated with a smaller decrease in bone mineral density; however, greater resistance and gains in both peripheral and central fat accumulation were recorded for the investigational drug. Bristol-Myers Squibb has discontinued its involvement in the development of BMS-986001, and future decisions on development will be made by Oncolys BioPharma. Funding: Bristol-Myers Squibb.